Answer:
You need to multiply the polynomials. Please see attached picture for answer.
= 4x ^4 + -10x^3 + 15x^2 + 7x +5
Step-by-step explanation:
You need to multiply each term step by step
(4x ^2+2x+1)*(x^2) + (4x ^2+2x+1)*(-3x) + (4x ^2+2x+1)*5
= (4x ^4 + 2x^3 +x^2) + (-12x ^3 - 6x^2 -3x) + (20x ^2+10x+5)
= 4x ^4 + -10x^3 + 15x^2 + 7x +5
Hey!
--------------------------------------------
Solution:
Remember to follow PEMDAS.
= (68 * 95) + 90 / 10
= (6,460) + 90 / 10
= 6,460 + 9
= 6,469
--------------------------------------------
Answer:
6,469
--------------------------------------------
Hope This Helped! Good Luck!
In order to find the answer to the question you will have to use PEMDAS and then solve.
Using PEMDAS:
Therefore your answer is "6469."
Hope this helps.
Answer:
Step-by-step explanation:
x = first number, y = second number
x + y = 80
y = 2x + 5
x + 2x + 5 = 80
3x + 5 = 80
3x = 80 - 5
3x = 75
x = 75/3
x = 25
y = 2x + 5
y = 2(25) + 5
y = 50 + 5
y = 55
so ur numbers are : 25 and 55 <==